Mothers of Multiples’ Perspectives on Fetal Reduction and Medical Abortion: Medical and Non-Medical Reasoning - Kelland, Jennifer; Ricciardelli, Rosemary (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
The issue of fetal reduction (aborting one or more fetuses in a multiple pregnancy) hasreceived much media attention in Canada (Blackwell), the United States (Hutchison;Padawer 2011b) and the United Kingdom (Newell; Padawer 2011a). Publicattention, combined with growing institutional and personal concerns about thehigh-risk nature of a multiple pregnancy (e.g., for the fetuses, the mother, healthcareresources, and marital strain) create the social foundation for this study. In interviewing41 mothers of multiples (e.g., mothers of twins and triplets) we sought toexplain how decision-making is based on medical and non-medical reasoning. Viewsof fetal reduction or fetal termination for non-medical reasons (e.g., the decision toterminate a pregnancy for lifestyle or personal reasons) were contrasted with views offetal reduction or fetal termination for medical reason (i.e., the decision to terminate apregnancy due to medical “problems”). Participants recognized that decision-makingrelated to selective reduction was a complex issue; however, all disagreed with theselective reduction of a twin to singleton pregnancy for non-medical reasons. A verysmall number of participants disclosed undergoing fetal reduction.